THEORETICAL FOUNDATIONS OF INNOVATION IN ENTREPRENEURSHIP - Muxammadiyeva, Dilafruz Alisher qizi; Sayfullayev, Сирожжон (THE INNOVATION ECONOMY, 2026)
The article examines the theoretical foundations of innovations in entrepreneurial activity. The study analyzes the concept and types of innovations, as well as their role in the entrepreneurial process. In addition, the mechanisms for implementing innovations and their impact on enterprise efficiency are identified. The research results indicate that innovations are a key driver of entrepreneurial development and contribute to improving economic efficiency.